-9b+10=-7b

Simple and best practice solution for -9b+10=-7b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9b+10=-7b equation:



-9b+10=-7b
We move all terms to the left:
-9b+10-(-7b)=0
We get rid of parentheses
-9b+7b+10=0
We add all the numbers together, and all the variables
-2b+10=0
We move all terms containing b to the left, all other terms to the right
-2b=-10
b=-10/-2
b=+5

See similar equations:

| 12+7n=16 | | j-–93=570 | | 0.05(x-150)=240 | | 5(9x+4)=3(4x+30) | | 8^(x+2)=(1/32)^(-5x) | | 6x-8-2x=6x-7 | | 15n-5n+6n=3n-1-4n | | x/9+10=13 | | 196=t7+ 182 | | 9g-1=-7+8g | | 12=7n=16 | | x+1/2=1/3x | | 4x(4x-12)=16x4 | | 12(x–4)+3(8x+2)=50x–77 | | (x+7)=(2x+1) | | x+20-5x=7(3+x)+x-8 | | 12n-7=16 | | c-177=592 | | 2x+72=140 | | 3r-6=r-10 | | 4(x-1)-3(x+1)=0 | | 7+7x=-8+2(4+4x) | | 2j+290=950 | | -v=13.9 | | 3x-43=122 | | 5(9x+4)=3(4x+9) | | 12x-7x+5x=8(2x+1)+x-8 | | {w}{2}w2-18=-7 | | -13=-b-7 | | -f=-12.7 | | d/5=7.2 | | -f=-12.6 |

Equations solver categories